PROBLEMS INHERENT IN THE ABSTRACT NATURE OF GENERAL DISTRIBUTION RULE OF THE BURDEN OF PROOF IN CIVIL PROCEEDINGS - Tamosiuniene, Egidija; Terebeiza, Zilvinas (European Scientific Journal, ESJ, 2013)
The burden of proof in civil proceedings is distributed between the parties following the general distribution rule of the burden of proof, meaning that each party has to prove the circumstances constituting the basis for its claim and objections. Such an abstract content of the distribution of the burden of proof, however, does not always reveal the answer to the question who carries the burden of proof. The impression can, therefore, be created that following the distribution rule for the burden of proof under discussion, each party has to prove the presence or absence of a fact. If we assumed, however, that substantiation of the same fact is a commitment of each opposing party, it would remain unclear who would have to bear the negative procedural legal consequences of failure to comply with or improper compliance with the burden of proof. Therefore, it is necessary to detail the general distribution rule of the burden of proof by identifying objective criteria to be invoked in deciding the issue of distribution of the burden of proof.